Freddie and Flossie - Hope, Laura Lee.; Pyle, Chuck, 1954- (New York : Aladdin, 2006)
Introduces Freddie and Flossie, in simple text with illustrations, describing the different things they like to do when they play.
"Spotlight"--T.p. verso.
1.4
K-3
Keywords: Bobbsey Twins (Fictitious characters) -- Fiction; Twins -- Fiction; Brothers and sisters -- Fiction; Play -- Fiction; Bobbsey Twins (Fictitious characters) -- Fiction; Twins -- Fiction; Brothers and sisters -- Fiction; Play -- Fiction; Bobbsey Twins (Fictional characters) -- Fiction; Twins -- Fiction; Siblings -- Fiction; Play -- Fiction